Una carta misiva de Juan de Albret anunciando la muerte de César Borgia - Panizo Santos, Ignacio (Huarte de San Juan. Geografía e Historia, 2007)
The author publishes a letter of Juan de Albret, last king of Navarre, to the duke of Frias, notifying the death of Cesar Borgia.